“Desarrollo de un sistema informático para la gestión de la documentación histórica del rectorado de la Universidad Técnica de Cotopaxi aplicando Isad (g) y .net” - Orellana Cabrera, Dennis Samuel (2023)
Currently, any institution, organization or entity, whether public or private, handles a large amount of information, which is stored and evidenced through documentation, this ultimately represents an important aspect for improvement, speaking at an educational level. more specifically in universities, there is a need where the administration and conservation of documents tend to be of total interest, since they consist of a functional organic structure, where each department and area has its files classified in a different way, in most Sometimes it is organized incorrectly or even worse, processes are physically maintained. For this, mention is made of the term document management that facilitates effective and systematic control over the creation, reception, maintenance, use and elimination of documents, avoiding the loss of information, loss of time and ensuring it. Therefore, the project focuses on the development of a computer system for the management of the historical documentation of the rectorate of the Technical University of Cotopaxi applying the ISAD (g) archival classification standard and the .NET development technology.